PENGARUH RETURN ON EQUITY, EARNING PER SHARE, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rinto, Muhamd; Susilowati, Dwi; Hernadi Moorcy, Nadi (Fakultas Ekonomi Universitas Balikpapan, 2024)
Muhamad Rinto (2023). The Effect of Return on Equity, Earning Per Share, and Debt to Equity Ratio on Stock Prices in Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange. Advisor: Mrs. Dwi Susilowati and Mr. Nadi Hernadi Moorcy. The purpose of this study was to determine the effect of Return on Equity, Earning Per Share, and Debt to Equity Ratio partially on Stock Price. The population in this study were 30 companies and a sample of 21 Food and Beverage subsector companies listed on the Indonesia Stock Exchange which were taken using the criteria determined by the author. The data analysis method used is multiple linear regression. The results of the t test are Return on Equity and Earning Per Share have a positive direction of relationship and have a significant effect on Stock Price while Debt to Equity Ratio has a negative and insignificant direction of relationship to Stock Price in Food and Beverage subsector companies listed on the Indonesia Stock Exchange.